Monoarticular antigen-induced arthritis leads to pronounced bilateral upregulation of the expression of neurokinin 1 and bradykinin 2 receptors in dorsal root ganglion neurons of rats - Segond von Banchet, Gisela (BioMed Central, 2000)
INTRODUCTION: Ongoing pain and hyperalgesia (enhanced pain response to stimulation of the tissue) are major symptoms of arthritis. Arthritic pain results from the activation and sensitization of primary afferent nociceptive nerve fibres ('pain fibres') supplying the tissue (peripheral sensitization) and from the activation and sensitization of nociceptive neurons in the central nervous system (central sensitization). After sensitization, nociceptive neurons respond more strongly to mechanical and thermal stimulation of the tissue, and their activation threshold is lowered. The activation and sensitization of primary afferent fibres results from the action of inflammatory mediators such as bradykinin (BK), prostaglandins and others on membrane receptors located on these neurons. BK is a potent pain-producing substance that is contained in inflammatory exudates. Up to 50% of the primary afferent nerve fibres have receptors for BK. When primary afferent nerve fibres are activated they can release neuropeptides such as substance P (SP) and calcitonin gene-related peptide from their sensory endings in the tissue. SP contributes to the inflammatory changes in the innervated tissue (neurogenic inflammation), and it might also support the sensitization of nociceptive nerve fibres by binding to neurokinin 1 (NK1) receptors. NK1 receptors are normally expressed on a small proportion of the primary afferent nerve fibres. AIMS: Because the expression of receptors on the primary afferent neurons is essential for the pain-producing action of inflammatory mediators and neuropeptides, we investigated in the present study whether the expression of BK and NK1 receptors on primary afferent neurons is altered during the acute and chronic phases of an antigen-induced arthritis (AIA). AIA resembles in many aspects the inflammatory process of human rheumatoid arthritis. Because peptide receptors are expressed not only in the terminals of the primary afferent units but also in the cell bodies, we removed dorsal root ganglia (DRGs) of both sides from control rats and from rats with the acute or chronic phase of AIA and determined, after short-term culture of the neurons, the proportion of DRG neurons that expressed the receptors in the different phases of AIA. We also characterized the inflammatory process and the nociceptive behaviour of the rats in the course of AIA. MATERIALS AND METHODS: In 33 female Lewis rats 10 weeks old, AIA was induced in the right knee joint. First the rats were immunized in two steps with methylated bovine serum albumin (m-BSA) emulsified with Freund's complete adjuvant, and heat-inactivated Bordetella pertussis. After immunization, m-BSA was injected into the right knee joint cavity to induce arthritis. The joint swelling was measured at regular intervals. Nociceptive (pain) responses to mechanical stimulation of the injected and the contralateral knee were monitored in the course of AIA. Groups of rats were killed at different time points after the induction of AIA, and inflammation and destruction in the knee joint were graded by histological examination. The DRGs of both sides were dissected from segments L1–L5 and C1–C7 from arthritic rats, from eight immunized rats without arthritis and from ten normal control rats. Excised DRGs were dissociated into single cells which were cultured for 18 h. The expression of the receptors was determined by assessment of the binding of SP-gold or BK-gold to the cultured neurons. For this purpose the cells were slightly fixed. Binding of SP-gold or BK-gold was detected by using enhancement with silver and subsequent densitometric analysis of the relative grey values of the neurons. Displacement controls were performed with SP, the specific NK1 receptor agonist [Sar(9), Met(O(2))(11)]-SP, BK, the specific BK 1 (B1) receptor agonist (D)-Arg (Hyp(3)-Thi(5,8)-(D)-Phe(7))-BK and the specific BK 2 (B2) receptor agonist (Des-Arg(10))-Lys-BK. RESULTS: The inflammatory process in the injected right knee joint started on the first day after induction of AIA and persisted throughout the observation period of 84 days (Fig. 1). The initial phase of AIA was characterized by strong joint swelling and a predominantly granulocytic infiltration of the synovial membrane and the joint cavity (acute inflammatory changes). In the later phases of AIA (10–84 days after induction of AIA) the joint showed persistent swelling, and signs of chronic arthritic alterations such as infiltration of mononuclear leucocytes, hyperplasia of synovial lining layer (pannus formation) and erosions of cartilage and bone were predominant. The contralateral knee joints appeared normal at all time points. Destruction was observed only in the injected knee but some proteoglycan loss was also noted in the non-injected, contralateral knee. In the acute and initial chronic phases of AIA (1–29 days) the rats showed mechanical hyperalgesia in the inflamed knee (limping, withdrawal response to gentle pressure onto the knee). In the acute phase (up to 9 days) a pain response was also seen when gentle pressure was applied to the contralateral knee. Figure 2 displays the changes in the receptor expression in the DRG neurons during AIA. The expression of SP–gold-binding sites in lumbar DRG neurons (Fig. 2a) was substantially increased in the acute phase of arthritis. In untreated control rats (n = 5), 7.7 ± 3.8% of the DRG neurons from the right side and 10.0 ± 1.7% of the DRG neurons from the left side showed labelling with SP–gold. The proportion of SP–gold-labelled neurons in immunized animals without knee injection (n = 3) was similar. By contrast, at days 1 (n = 2 rats) and 3 (n = 5 rats) of AIA in the right knee, approximately 50% of the DRG neurons exhibited labelling with SP–gold, and this was seen both on the side of the injected knee and on the opposite side. At day 10 of AIA (n = 3 rats), 26.3 ± 6.1% of the ipsilateral DRG neurons but only 15.7 ± 0.6% of the contralateral neurons exhibited binding of SP–gold. At days 21 (n = 5 rats), 42 (n = 3 rats) and 84 (n = 5 rats) of AIA, the proportion of SP–gold-positive neurons had returned to the control values, although the arthritis, now with signs of chronic inflammation, was still present. Compared with the DRG neurons of the untreated control rats, the increase in the proportion of labelled neurons was significant on both sides in the acute phase (days 1 and 3) and the intermediate phase (day 10) of AIA (Mann–Whitney U-test). The size distribution of the neurons was similar in the DRG neurons of all experimental groups. Under all conditions and at all time points, SP–gold binding was found mainly in small and medium-sized (less than 700 μm(2)) neurons. In the cervical DRGs the expression of NK1 receptors did not change in the course of AIA. The binding of SP–gold to the neurons was suppressed by the coadministration of the specific NK1 receptor agonist [Sar(9), Met(O(2))(11)]–SP in three experiments, showing that SP–gold was bound to NK1 receptors. The expression of BK–gold-binding sites in the lumbar DRG neurons showed also changes in the course of AIA, but the pattern was different (Fig. 2b). In untreated control rats (n = 5), 42.3 ± 3.1% of the DRG neurons of the right side and 39.6 ± 2.6% of the DRG neurons of the left side showed binding of BK–gold. At days 1 (n = 2 rats) and 3 (n = 5 rats) of AIA, approximately 80% of the DRG neurons on the side of the knee injection (ipsilateral) and approximately 70% on the opposite side were labelled. In comparison with the untreated control group, the increase in the proportion of labelled neurons was significant on both sides. The proportion of labelled neurons in the ipsilateral DRGs remained significantly increased in both the intermediate phase (day 10, n = 3 rats) and chronic phase (days 21, n = 5 rats, and 42, n = 3 rats) of inflammation. At 84 days after the induction of AIA (n = 5 rats), 51.0 ± 12.7% of the neurons showed an expression of BK–gold-binding sites and this was close to the prearthritic values. However, in the contralateral DRG of the same animals the proportion of BK–gold-labelled neurons declined in the intermediate phase (day 10) and chronic phase (days 21–84) of AIA and was not significantly different from the control value. Thus the increase in BK–gold-labelled neurons was persistent on the side where the inflammation had been induced, and transient on the opposite side. The size distribution of the DRG neurons of the different experimental groups was similar. In the cervical DRGs the expression of BK receptors did not change in the course of AIA. In another series of experiments, we determined the subtype(s) of BK receptor(s) that were expressed in DRGs L1–L5 in different experimental groups. In neither untreated control animals (n = 5) nor immunized rats without knee injection (n = 5) nor in rats at 3 days (n = 5) and 42 days (n = 5) of AIA was the binding of BK–gold decreased by the coadministration of BK–gold and the B1 agonist. By contrast, in these experimental groups the binding of BK–gold was suppressed by the coadministration of the B2 agonist. These results show that B2 receptors, but not B1 receptors, were expressed in both normal animals and in animals with AIA. DISCUSSION: These results show that in AIA in the rat the expression of SP-binding and BK-binding sites in the perikarya of DRGs L1–L5 is markedly upregulated in the course of knee inflammation. Although the inflammation was induced on one side only, the initial changes in the binding sites were found in the lumbar DRGs of both sides. No upregulation of SP-binding or BK-binding sites was observed in the cervical DRGs. The expression of SP-binding sites was upregulated only in the first days of AIA, that is, in the acute phase, in which the pain responses to mechanical stimulation were most pronounced. By contrast, the upregulation of BK-binding sites on the side of AIA persisted for up to 42 days, that is, in the acute and chronic phase of AIA. Only the B2 receptor, not the B1 receptor, was upregulated. The coincidence of the enhanced expression of NK1 and BK receptors on sensory neurons and the pain behaviour suggests that the upregulation of these receptors is relevant for the generation and maintenance of arthritic pain. In the acute phase of AIA, approximately 50% of the lumbar DRG neurons showed an expression of SP-binding sites. Because peptide receptors are transported to the periphery, the marked upregulation of SP-binding receptors probably leads to an enhanced density of receptors in the sensory endings of the primary afferent units. This will permit SP to sensitize more neurons under inflammatory conditions than under normal conditions. However, the expression of NK1 receptors was upregulated only in the acute phase of inflammation, suggesting that SP and NK1 receptors are less important for the generation of hyperalgesia in the chronic phase of AIA. Because BK is one of the most potent algesic compounds, the functional consequence of the upregulation of BK receptors is likely to be of immediate importance for the generation and maintenance of inflammatory pain. The persistence of the upregulation of BK receptors on the side of inflammation suggests that BK receptors should be an interesting target for pain treatment in the acute and chronic phases. Only B2 receptors were identified in normal animals and in rats with AIA. This is surprising because previous pharmacological studies have provided evidence that, during inflammation, B1 receptors can be newly expressed. Receptor upregulation in the acute phase of AIA was bilateral and almost symmetrical. However, hyperalgesia was much more pronounced on the inflamed side. It is most likely that receptors on the contralateral side were not readily activated because in the absence of gross inflammation the local concentration of the ligands BK and SP was probably quite low. We hypothesize that the bilateral changes in receptor expression are generated at least in part by mechanisms involving the nervous system. Symmetrical segmental changes can be produced only by the symmetrical innervation, involving either the sympathetic nervous system or the primary afferent fibres. Under inflammatory conditions, primary afferent fibres can be antidromically activated bilaterally in the entry zone of afferent fibres in the spinal cord, and it was proposed that this antidromic activation might release neuropeptides and thus contribute to neurogenic inflammation. Because both sympathetic efferent fibres and primary afferent nerve fibres can aggravate inflammatory symptoms, it is also conceivable that they are involved in the regulation of receptor expression in primary afferent neurons. A neurogenic mechanism might also have been responsible for the bilateral degradation of articular cartilage in the present study.